2017
DOI: 10.1093/icb/icx102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Decoupling of Thermal Hardiness across Metamorphosis in Drosophila melanogaster

Abstract: As organisms age the environment fluctuates, exerting differential selection across ontogeny. In particular, highly seasonal environments expose life stages to often drastically different thermal environments. This developmental variation is particularly striking in organisms with complex life cycles, wherein life history stages also exhibit distinct morphologies, physiologies, and behaviors. Genes acting pleiotropically on thermal responses may produce genetic correlations across ontogeny, constraining the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 71 publications
4
44
0
Order By: Relevance
“…Selection on larval and adult ability to resist extreme temperatures showed these traits are independent in Drosophila buzzatii flies [30] and in the butterfly Bicyclus anynana [31]. Phenomenological independence between temperature-stress resistance in insect larvae and adults is congruent with the recent discovery that, at the genome level, different combinations of genes affect cold hardiness in larvae and in adults in Drosophila melanogaster [32]. Even functionally related traits measured in the same organism can exhibit very different levels of genetic correlation.…”
Section: Empirical Studies Of Genetic Constraints Between Life Stagesmentioning
confidence: 62%
“…Selection on larval and adult ability to resist extreme temperatures showed these traits are independent in Drosophila buzzatii flies [30] and in the butterfly Bicyclus anynana [31]. Phenomenological independence between temperature-stress resistance in insect larvae and adults is congruent with the recent discovery that, at the genome level, different combinations of genes affect cold hardiness in larvae and in adults in Drosophila melanogaster [32]. Even functionally related traits measured in the same organism can exhibit very different levels of genetic correlation.…”
Section: Empirical Studies Of Genetic Constraints Between Life Stagesmentioning
confidence: 62%
“…2016; Freda et al. 2017; Teets and Hahn 2018). Here we measured correlations between several cold tolerance traits and found them to be sparse and sex‐specific.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal failure operationally defines both CT min and CT max (Andersen et al, 2018;Andersen and Overgaard, 2019;Jørgensen et al, 2019), and dynamic stabilization of the neuromuscular circuit under temperature stress is a likely mechanism for altering thermal limits. Indeed, previous investigation of the genetic architecture of cold hardiness and electrophysiological analyses of the rapid hardening response both suggest an important role for stabilization of ion channels and cytoskeletal structures supporting the synapse and neuromuscular junction (Klose and Robertson, 2004;Robertson and Money, 2012;Freda et al, 2017). Aside from genes involved in neural morphogenesis, the GO term extracellular structure organization was overrepresented among cold tolerance genes, and this was the only overrepresented category that did not overlap with the differential expression categories.…”
Section: H3: Genes Involved In Thermal Tolerance Affect the Developmementioning
confidence: 95%
“…For example, two plastic responses to cold, rapid cold hardening and developmental cold acclimation, have non-overlapping SNPs associated with them, although the genes associated with these traits share some functional similarities (Gerken et al, 2015). Similarly, Teets and Hahn (2018) found minimal overlap in genes associated with cold shock response and chill coma recovery, and Freda et al (2017) found no overlap in genes associated with adult and larval cold hardiness. The candidate genes identified in Teets and Hahn (2018) were functionally tested with RNAi, and knockdown of most genes affected cold tolerance, indicating that GWAS is a robust method for identifying genes with functional roles in thermal tolerance.…”
Section: Introductionmentioning
confidence: 99%